Perspectives of Jordanian men about lower urinary tract assessment and physiotherapy interventions: A cross-sectional study - Darabseh, Mohammad Z; Aburub, Aseel; Aries, Ali; Awwad, Shorooq; Khalil, Hanan (International Journal of Innovative Research and Scientific Studies, 2025)
There is a significant gap in understanding the impact of physiotherapy interventions on men with urinary incontinence (UI). Conducting clinical trials in this area is costly, time-consuming, and difficult. Before embarking on such trials, it is crucial to gather insights into men's perceptions regarding UI assessment and the acceptance of physiotherapy interventions. Therefore, this study aimed to explore the perspectives of Jordanian men about lower urinary tract assessment and physiotherapy interventions. An online survey was distributed through social media platforms targeting men's groups in Jordan, yielding responses from 421 participants. The results indicated that a majority of respondents found it acceptable to undergo assessments involving history taking (74%), voiding diaries (73%), and the pad test (71%). Furthermore, a significant number expressed a willingness to engage in pelvic floor exercises (83%) and behavioral therapy (85%). However, a notable proportion of participants deemed certain assessment methods unacceptable, including ultrasound examination of the anal sphincter (70%), palpation of the bulbocavernosus muscle via the perineum (73%), and electrical stimulation (98%) for future research participation. Overall, approximately three-quarters of the Jordanian men surveyed indicated a willingness to participate in research studies focused on physiotherapy management for UI, while specific techniques such as ultrasound, palpation of the bulbocavernosus muscle via the perineum, and electrical stimulation were not deemed acceptable techniques for use in research.